(untitled) (International Journal of Studies in Nursing, 2021)
Aim: To investigate the knowledge and attitudes of nurses towards older adults in the Taiwanese hospital. Design: A descriptive correctional study. Methods: A survey by random sampling of one teaching hospital for clinical nurses (N=80). The structural scales included demographic details, Palmore’s Facts on Aging Quiz (PFAQ) knowledge scale, and Kogan’s Old People (KOP) attitude scale. Lastly, we used Pearson’s correlation analyses to identify the correlates. Results: The rate of knowledge about aging was low at 55.76%. However, the subjects held more favorable attitudes towards older adults (KOP score was 66.91). We also found that subjects who had better knowledge about aging also had a more positive attitude towards older adults. The results can be used by nursing educators and managers to design courses on gerontology for nurses and nursing students, by providing data that can be utilized in decision-making regarding the effectiveness of nursing care provided to this growing group of older recipients.